Intersection, interrelation or interdependence? The relationship between circular economy and nexus approach. (1st September 2021) - Parsa, Ali; Van De Wiel, Marco J.; Schmutz, Ulrich
Abstract: Circular Economy (CE) and nexus thinking are increasingly considered as promising solutions for resource sustainability. While CE aims to design out waste through reducing, reusing, recycling and recovery of materials, the Nexus approach is interested to minimise waste and inefficiencies by focusing on the interlinkages between resources. Both concepts have been evolving separately with limited academic work to analyse their relationship. The aim of this systematic review, based on academic publications from 2004 to 2020, is to scrutinise the relationship between the circular economy and the nexus approach by adopting a mixed methods research design including bibliometric analysis and thematic synthesis. Our quantitative bibliometric analysis shows that, out of 7956 circular economy and 5795 nexus papers, academic documents explicitly mentioning both concepts account for less than 1% of each literature. Nonetheless, there is considerable overlap in most frequent words (50%–71%) as well as the most relevant sources (54%–56%) between both literatures. A detailed qualitative analysis of the documents relevant to both concepts also supports the existence of a close relationship between the two. From these analyses, we develop a new integrative conceptualization of the relationship between circular economy and the nexus approach. We conclude that there is good evidence for a three-tiered hierarchical relationship: 'intersection', 'interrelation' and 'interdependence', which we discuss in detail. Finally, emphasising the importance of an integrated approach, we propose a novel conceptual framework which combines circular economy and nexus approaches, which helps to operationalise nexus thinking on the one hand, and to converge the circular economy towards environmental sustainability on the other hand. As such, the framework addresses two known challenges of the concepts. However, whilst our integrated framework contributes to the conceptual development of both circular economy and the nexus approach, further research is required to highlight and facilitate their interrelation and interdependence in practice.